MOTIVASI, KOMITMEN ORGANISASIONAL DAN KEPUASAN KERJA KARYAWAN DI WAROENG SPESIAL SAMBAL, JATINANGOR - Kalifatullah Ermaya, Sir; Mujdalipah, Siti (Coopetition : Jurnal Ilmiah Manajemen, 2019)
The food service industry has received many challenges in the current era of disruption of the industrial revolution 4.0. Given the urgency of increasing the Motivation and Organizational Commitment in one of the restaurants in Jatinangor, the title of this study is "Motivation, Organizational Commitment and Job Satisfaction in Waroeng Spesial Sambal, Jatinangor". This research belongs to the category of associative causal research using a quantitative approach. The results showed: 1. Motivation partially has a significant effect on the Employee Satisfaction variable; 2. Organizational Commitment partially has no effect and isn?t significant on the Employee Satisfaction variable; 3. Motivation and Organizational Commitment simultaneously have a positive and significant effect on the Employee Satisfaction variable.